2020
DOI: 10.4236/jdm.2020.103014
|View full text |Cite
|
Sign up to set email alerts
|

Association of NFkB1 Gene Polymorphism with Inflammatory Markers in Patients of Type 2 Diabetes Mellitus with or without Renal Involvement in Eastern India

Abstract: Aims: To evaluate the association of Nuclear factor kappa B1(NFkB1) gene polymorphism with inflammatory markers Urinary Monocyte Chemoattractant Protein 1 (UMCP1) and Tumor Necrosis Factor alfa (TNF alfa) in Patients of diabetes mellitus with or without renal involvement in Eastern India. Material and Methods: Consecutive Patients of Type 2 Diabetes Mellitus (DM) with or without microalbuminuria attending SCB MEDICAL COLLEGE and HOSPITAL Medical OPDs in between September 2018 to September 2019 were recruited i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Several studies have reported elevated levels of serum TNF in DN patients and T2DM. In addition, the relationship was further confirmed in a meta-analysis ( 23 ). However, there is limited information on the mechanisms underlying the elevated inflammatory markers in DN and T2DM.…”
Section: Discussionmentioning
confidence: 78%
“…Several studies have reported elevated levels of serum TNF in DN patients and T2DM. In addition, the relationship was further confirmed in a meta-analysis ( 23 ). However, there is limited information on the mechanisms underlying the elevated inflammatory markers in DN and T2DM.…”
Section: Discussionmentioning
confidence: 78%
“…Hyperglycemia promotes the formation of advanced glycation end-products (AGEs) that induce inflammation and oxidative stress, so polymorphisms in the AGER gene have been associated with the risk of type 2 diabetes ( Kang et al, 2012 ; Lin et al, 2012 ). In addition, the inhibition of the NFKB1 and NFKB2 genes shows a decrease in the inflammatory process, consequently improving hypertension and suppressing vasoconstriction induced by diabetes ( Gautam et al, 2017 ; Behera et al, 2020 ). In patients with T2DM, we can also observe an increased expression of the FTO gene, which may be involved in oxidative metabolism, lipogenesis, and oxidative stress ( Bravard et al, 2011 ).…”
Section: Genes Related To Type 2 Diabetes Mellitusmentioning
confidence: 99%